Dampak status sosial ekonomi terhadap hasil belajar siswa menggunakan metode systematic literature review - ST. Rohmah; Silvia Yulian Sah; Mohammad Edy Nurtamam (Universitas Sebelas Maret, 2025)
This study aims to analyse the impact of socioeconomic status on students' learning outcomes and explore factors that can mitigate academic disparities resulting from economic differences. The research method employed is a Systematic Literature Review (SLR), analysing 20 journal articles selected based on inclusion criteria such as topic relevance, publication year (2014–2024), and clearly defined research methods. Data were gathered through Google Scholar using Publish or Perish (PoP) and subsequently screened with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) diagram to ensure validity. Data analysis was carried out using a thematic approach to identify patterns and trends in relevant research. The findings reveal that students from higher socioeconomic backgrounds have greater access to educational facilities, while those from lower socioeconomic backgrounds often face resource constraints and limited parental academic support. However, learning motivation, a supportive school environment, and adaptive teaching strategies can help bridge academic disparities. The study concludes that more inclusive educational policies are essential, such as scholarship provision, improvements in school quality, and parental education programmes. This study recommends developing targeted support programmes for students from disadvantaged backgrounds to foster equitable learning opportunities.